Efecto del pienso sobre la produccion de la coneja a una temperatura ambiente alta - Simplicio, J.B.=700 1 Fernandez-Carmona, J.; Cervera, C.; Blas, E.
(Es, En)
ilus., 12 ref.
Keywords: CONEJO (ORYCTOLAGUS); TEMPERATURA AMBIENTAL; ENERGIA; PRODUCCION; PIENSOS; ESPAÑA